Extrapulmonic presentation of tuberculosis: An atypical urogenital presentation of a common disease - Matthew Pagni, MD; Matthew Thompson, MD; Kacy Ramirez, MD; George Koberlein, MD (Radiology Case Reports, 2020)
Mycobacterium tuberculosis is the leading cause of infectious disease-related death worldwide. However, it is less frequently encountered in developed countries, and 90% of cases are reported in adults, making it a less commonly encountered entity in pediatric radiology. The disease is treatable, but symptoms of renal disease are nonspecific and should be identified early. A high index of clinical suspicion and supportive imaging studies, particularly in immigrant or exposed children, is prudent to prevent irreversible organ damage. We report a rare case of a 16-year-old Mexican immigrant male who presented with chronic dysuria, urinary frequency, intermittent hematuria, hydronephrosis, ureteral stenosis, and evolving autonephrectomy secondary to renal M. tuberculosis. Keywords: Pediatric, Tuberculosis, Infectious disease, Genito-urinary